New Way to Go: Hybrid Coronary Revascularization (CABG) - Sazzad, Md Faizus (Society of Minimally Invasive Cardiovascular And thoracic Surgeons of India (SMICTSI), 2021)
2nd Annual Conference of the Society of Minimally Invasive Cardiovascular And thoracic Surgeons of India (SMICTSI)